Reactive Arthritis from Influenza Vaccination: A Novel Presentation That Mimics Prosthetic Joint Infection. Issue 4 (October 2021) - Bell, Douglas; Manchal, Naveen; McNamara, John; McDougall, Catherine
Abstract : Case: A 50-year-old woman with a history of bilateral knee replacements developed acute-onset bilateral painful knee effusions and inability to weight-bear. She was systemically well, but 2 days before the onset of her symptoms, she received an influenza vaccination. Synovial fluid analysis revealed white cell count (WCC) 190, 000 × 10 9, 85% polymorphomuclear lymphocytes (PMN) on the left knee and WCC 252, 200 × 10 9, 89% PMN on the right knee. Debridement and implant retention and polyethylene exchange was performed. Extended bacterial culture was negative as was 16s RNA polymerase chain reaction for remnants of bacterial DNA. No crystals were seen on any specimen. Both knees are stable and pain free at 12-month follow-up. Conclusion: Reactive arthritis secondary to influenza vaccination is a rare condition that can mimic prosthetic joint infection.